Developing multimedia-based learning media on the digestive system using Adobe Flash Professional CS6 application for class XI - Muhammad Fakhrul Arifin; Aditya Rahman; Mila Ermila Hendriyani; Ika Rifqiawatia (Universitas Muhammadiyah Malang, 2022)
This study aims to develop and test the feasibility of multimedia-based learning media for the concept of the human digestive system using Adobe Flash Professional CS6. This research and development (R&D) use the ADDIE development model. The development carried out in this study is limited to the 7th step, including problem identification, data collection, product design, design validation, design revision, product testing, and product revision. The subjects of this study were determined by using random sampling. Data collection was carried out by non-test techniques using interview guide sheets, validation questionnaires from media and material experts, and student response questionnaires. The results showed that the feasibility test of the product developed based on the material was in the excellent category of 91%. Furthermore, the results showed that the feasibility test of the product developed based on the assessment of media experts was feasible with 87.5%. User-based due diligence through limited trial also showed decent results with 97.7%. These results indicate that the multimedia-based learning media developed using Adobe Flash Professional CS6 is feasible for mass production after the final revision.